2021
DOI: 10.3389/fphys.2021.751501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ellagic Acid on Hepatic Lipid Metabolism and Antioxidant Activity in Mice

Abstract: Accumulating evidence has demonstrated that the imbalance of lipid metabolism and antioxidant capacity leads to damage to liver. The present study aimed to investigate the effects of ellagic acid (EA), a phenolic compound, on hepatic lipid metabolism and antioxidant activity in mice. In our study, 24 C57BL/6J mice were divided into three groups: (1) control (CON); (2) basal diet+0.1% EA (EA1); and (3) basal diet+0.3% EA (EA2). After the 14-day experiment, the liver was sampled for analysis. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Particularly, abnormalities in lipid profile or regulation can lead to abnormalities in inflammatory responses, and the reverse is also true in that alterations of inflammatory signaling (in the context of metabolic diseases such as diabetes or atherosclerosis) can result in changes of lipid metabolism in liver, skeletal muscle, macrophage, or adipose tissue (Glass & Olefsky, 2012). In a murine basal diet model, EA supplementation decreased total cholesterol, low-density lipoprotein, and the abundance of acetyl-CoA carboxylase while increasing high-density lipoprotein and the abundances of phospho-hormone-sensitive lipase, carnitine palmitoyl transferase 1B, and peroxisome proliferator-activated receptor alpha protein (Xu et al, 2021). In a randomized double-blind clinical trial, patients with type 2 diabetes consuming 180 mg of EA daily for 8 weeks demonstrated a decrease in inflammatory markers (i.e, TNF, and IL-6), total cholesterol, triglycerides, as well as low-density lipoprotein and an increase in total antioxidant capacity, glutathione peroxidase activity, as well as superoxide dismutase enzymes (Ghadimi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, abnormalities in lipid profile or regulation can lead to abnormalities in inflammatory responses, and the reverse is also true in that alterations of inflammatory signaling (in the context of metabolic diseases such as diabetes or atherosclerosis) can result in changes of lipid metabolism in liver, skeletal muscle, macrophage, or adipose tissue (Glass & Olefsky, 2012). In a murine basal diet model, EA supplementation decreased total cholesterol, low-density lipoprotein, and the abundance of acetyl-CoA carboxylase while increasing high-density lipoprotein and the abundances of phospho-hormone-sensitive lipase, carnitine palmitoyl transferase 1B, and peroxisome proliferator-activated receptor alpha protein (Xu et al, 2021). In a randomized double-blind clinical trial, patients with type 2 diabetes consuming 180 mg of EA daily for 8 weeks demonstrated a decrease in inflammatory markers (i.e, TNF, and IL-6), total cholesterol, triglycerides, as well as low-density lipoprotein and an increase in total antioxidant capacity, glutathione peroxidase activity, as well as superoxide dismutase enzymes (Ghadimi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…5c), which together, potentiated the potent antioxidant action of the purified tannin. Moreover, an ellagitannins‐rich dietary supplement from pomegranate has been shown to suppress lipid peroxidation in obese individuals (Heber et al ., 2007), while commercial ellagic has been shown to exert anti‐lipid peroxidative activity in obese animals (Xu et al ., 2021). Also, the antioxidant properties gallic (Gao et al ., 2019), as well as quercetin and its glucosides (Terao, 2023) have been documented.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the generation of urolithins in almost all mammals after ETs are consumed, there are also some animal species (e.g., pigs and rats) that are able to produce dehydroxyellagic acid derivatives, namely, nasutins [ 16 ]. After absorption by the intestine into the bloodstream, raspberry polyphenolic metabolites are first transported to the liver, where they can interact with molecular mechanisms involved in the regulation of metabolism, inflammation and oxidative stress [ 4 , 17 ]. One of the mechanisms that might be activated by raspberry polyphenols is related to the regulation of peroxisome proliferator-activated receptors (PPARs) and sterol regulatory element-binding protein 1c (SREBP-1c) in the liver [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%